RESPONSES OF GASOLINES TO METHANOL/TBA - Maizar Rahman; Widjoseno Kaslan; Atung Kontawa; Retno Ambarwati (Scientific Contributions Oil and Gas, 1988)
Low level alcohol-gasoline blends with normally under 10 vol% of alcohols are intended for use in the existing curs. Because the alcohols have differents properties than hydrocarbon components, their impact on critical gasoline properties have to be understood. This article discussed the research results on the properties of MEOH TBA (50/50) gasoline mixture at different alcohol levels using base fuels from different local refineries.